Analisis Kelayakan Usaha Ternak Sapi Potong Di Kecamatan Perbaungan - Sarma Wati; Sarah Devi; Sela Maharani; Nurul Sahara; Kiagus Muhammad Zain Basriwijaya (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
To find out the beef cattle business in Perbaungan sub-district is potentially profitable from a financial, social and environmental perspective. Primary data were collected through interviews with farmers and secondary data from relevant agencies. Descriptive-analytical method was used. Benefit-Cost Ratio (BCR), Net Present Value (NPV), and Internal Rate of Return (IRR) were used to assess business feasibility. The results showed that the beef cattle business is financially viable with a BCR value of 1.35, NPV of 25,000,000, and IRR of 18 per cent. In addition, the business has a positive impact on income generation, job creation, and farmer welfare. But there are some problems, such as changes in feed prices and cattle waste management. Even if feed prices and cattle selling prices change significantly, the business is still viable, according to the sensitivity analysis. To make the business more sustainable, the government should help through training programmes, feed subsidies and access to finance. Beef cattle enterprises have great potential to grow and have a positive impact on both the environment and the community if managed properly.